The Principle of Tauhid and Ownership in Islamic Economic - Mujahidin Mujahidin (IAIN Palopo, 2021)
The purpose of this study is to explore the principle of Tauhid in ownership in Islamic economics, Tauhid in Islam is recognized as a fundamental principle of religion or can be called the most basic principle in religion especially in the concept of Islamic economics. Research method is a Literature review is a systematic, explicit and reproducible method for identifying, evaluating and synthesizing works of research results and ideas that have been produced by researchers and practitioners. Literature review aims to make an analysis and synthesis of existing knowledge related to the topic to be researched to find empty space for research to be carried out. the results of this study found that Islam recognizes human nature to love wealth and own it. The wealth that is in the hands of humans is only a deposit and a mandate that must be fulfilled according to what the owner wants. The concept of ownership in Islam is very comprehensive, where Islam not only regulates how property ownership can be obtained in a lawful way, how property can be developed and utilized, but also regulates how property can function for the welfare of the people, namely by moving the owners to distribute to meet their needs. The concept of ownership in Islamic teachings departs from the view that humans have a basic tendency (fitrah) to own property individually, but also need other parties in their social life.